Diurnal Variation of Leukocytosis and its Prognostic Significance in Head Trauma in Local Population (Medical Forum Monthly, 2024)
Objective: To study the Predictive value of leukocytosis in minor, moderate and severe head trauma.Study Design: Prospective and analytical study.Place and Duration of Study: This study was conducted at the Department of Physiology, B.M.S.I in Accident and Emergency, ICU of Neurosurgery Department (ward -16) JMPC Karachi Pakistan from January 2009 to January 2011.Materials and Methods: 90 patients of head trauma were included, after taking complete history from the conscious patients and from the attendants of unconscious patients. Glass Coma Score were observed immediately with Glass Coma Score and blood sample was taken for white cell count with hemocytometer (Neubaur chamber), peripheral smear were prepared at the spot for differential leukocyte count within the time.Results: 90 patients of head trauma of age 16 to 70 years were included of either sex. Statistically the mean leukocyte count revealed that significantly higher as compared to minor and moderate (p <0.001)Conclusion: On admission, white blood cells (WBC) count exceeding 19000/ mm 3 has a predictive as well as value for poor Glasgow coma scale (GCS) and serves as a significant parameter of severity of injury and predicator neurological out coma in patients with moderate and severe head injury in localpopulation.